The Study of Implementation Effectiveness in the Various Criminal Law Policies During the Covid-19 Pandemic - Joko Sri Widodo; Kristiawanto Kristiawanto; Tofik Yanuar Chandra (Universitas Syiah Kuala, 2021)
There are various pros and cons to the criminal law policies by the Indonesian government in the context of dealing with covid 19. So it is necessary to have a study related to the effectiveness of implementing these various policies. The author's background is to discuss the formulation of the problem in this article: What is the criminal law policy during the covid 19 pandemic? And how is the effectiveness in the implementation of these policies? This article uses a normative juridical research method that examines various positive laws from the applicable laws and regulations, and then it is analyzed in analytical descriptive. The Indonesian government has established various policies to prevent the covid 19 transmission. The guidelines consist of: the formation of various legal regulations related to the covid pandemic; a policy of criminal sanctions for violators of social policies during the covid 19 pandemic; prisoner assimilation policy; electronic trial of criminal cases during the covid 19 pandemic; corruption prevention policies; policies on workplaces in public areas. Regarding the effectiveness of implementing these policies, it can be said that the execution tends to be less optimal because the policies are contrary to one another. So this article provides suggestions to the government and the community should have mutual support for the implementation of criminal law policies during the COVID-19 pandemic can be effective.